Age, gender and deterrability: Are younger male drivers more likely to discount the future?. (July 2017) - Freeman, James; Kaye, Sherrie-Anne; Truelove, Verity; Davey, Jeremy
Highlights: Explored the influence of discounting the future tendencies on self-report speeding. Examined which perceptual deterrent constructs had greatest influence on speeding. Discounting the future tendencies were predictive of lower perceptual certainty. Being male and having a tendency to discount the future influenced deterrence. Abstract: Utilizing the Classical Deterrence theory and Stafford and Warr's (1993) reconceptualized model of deterrence, the current study examined whether age, gender, and discounting the future tendencies influence perceptions of being apprehended for speeding offences. Licensed motorists ( N = 700; 57% female) in Queensland (Australia) were recruited to complete a self-report questionnaire that measured perceptual deterrence, speeding related behaviors and discounting the future tendencies. Data were analyzed utilizing descriptive, bivariate and multivariate regressions. Significant (albeit weak) positive correlations were found between age and perceptions of apprehension certainty. Males were significantly more likely to report higher incidences of speeding (including while avoiding detection) compared to females. In contrast, females were more likely to perceive high levels of apprehension certainty and consider impending penalties to be more severe. At a multivariate level, discounting the future tendencies (in addition to being male, reporting lower levels of perceptual severity and swiftness, and more instances of punishment avoidance) were predictive of lower perceptual certainty levels. This study is one of the first to reveal that being male and having a tendency to discount the consequences of the future may directly influence drivers' perceptual deterrence levels.